Circadian effects of scopolamine on memory, exploratory behavior, and muscarinic receptors in mouse brain - Pan Si-Yuan (Acta Pharmacologica Sinica, 2016)
Mice were maintained at light-dark cycle with lights on from 05:00-19:00 for 10 d in laboratory. The study was performed at 07:00-09:00, 15:00-17:00, and 21:00-23:00 in June and July. Scopolamine (Scop, 0.1 and 0.4 mg.kg-1, ip) was injected 15 min prior to training or the first exploratory test. The amnesic effects of Scop showed hyperresponses at 07:00-09:00 and 15:00-17:00, and hyporesponses at 21:00-23:00 using step-through and step-down tasks. The circadian effects of Scop on exploratory behavior were consistent with the findings above mentioned. The numbers of [3H]quinuclidinyl benzilate ([3H]QNB) binding sites in the temporal cortex and hippocampus were more at 08:00 and 16:00 than those at 22:00. However, muscarinic receptor levels in the striatum were lower at 08:00 than those at 22:00. These results indicated that the effects of Scop on memory, behavior in a novel environment, and muscarinic receptors in brain regions showed circadian changes in mice.